Pentingnya Peran Edukasi dan Sosialisasi Fisioterapi dalam Pencegahan Gangguan Neck Pain pada Pekerja Konveksi Baju di CV. Defix Unggul Jaya Kota Malang - Salsabila Fachraini Ritonga; Dimas Sondang Irawan (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The textile industry, especially clothing, is never-ending, because clothing is one of the primary needs, so that production services for ready-made clothing or the clothing convection industry continue to grow rapidly. One of the companies in the clothing convection industry in Malang City is CV. Defix Unggul Jaya. The clothing convection industry often shows intensive and repetitive work patterns. This can result in excessive workloads on workers, causing work-related diseases. Each stage of work in the clothing convection industry can cause risks related to work postures such as neck pain complaints. The incidence of neck pain complaints in workers reaches 6-67%. So the role of physiotherapy becomes very important, where the form of physiotherapy services not only provides treatment, but can provide services in the form of preventing neck pain disorders through socialization activities. The purpose of this socialization activity is to see the importance of the role of physiotherapy education in understanding the prevention of neck pain in CV. Defix Unggul Jaya, Malang City convection workers. The method used is education through socialization related to neck pain complaints using leaflets as a promotional media for the mat and using pre-test and post-test to determine the level of workers' understanding of neck pain complaints. The results obtained show an increase in the understanding of convection workers regarding the prevention and proper handling of neck pain.